Clogging vs. fouling in immersed membrane bioreactors. (1st November 2018) - Buzatu, P.; Qiblawey, H.; Odai, A.; Jamaleddin, J.; Nasser, M.; Judd, S.J.
Abstract: Whilst the fouling of MBR membrane surfaces has been very extensively explored by the academic community, there is an increasingly widespread recognition by practitioners of the issue of clogging of membrane channels with sludge solids, sometimes termed "sludging". The study undertaken has quantified this phenomenon using a bespoke test cell allowing a flat sheet membrane channel to be viewed directly during operation and the accumulated solids determined by digital image processing. Sludging behaviour has then been correlated both with the sludge properties, from sludge samples taken from both an industrial and municipal MBR, and the permeability decline rate data. The work has revealed the expected trends in fouling propensity, as quantified by the exponent n of the Δ p/ Δ t  =  m. exp( nJ ) correlation from classical flux-step tests. With zero membrane aeration the industrial samples exhibited sludging, the filling of the complete thickness of the membrane channel with sludge solids, whereas for municipal sludge the solids formed a cake layer which did not fill the channel. In the absence of sludging the permeability decline followed the expected pattern of increasing at the elevated soluble COD and capillary suction time values of the industrial sludge, compared with municipal sludge at the same solids concentration range (8–12 g.L −1 ). However, there was no evident correlation between fouling (permeability decline without sludging) and sludging: incipient sludging did not appear to influence permeability, though can be assumed to negatively impact on long-term operation, or relate to the sCOD concentration. Sludging instead appeared to depend on the sludge physical properties, and primarily the viscosity: sludge samples at high viscosities were found to exhibit a different air-scour pattern to that at normal MLSS concentrations. Outcomes suggest that sludging is caused by rheological conditions promoting bubble coalescence and bubble stream constriction, reducing the exposure of the membrane surface to scouring air. Graphical abstract: Image Highlights: Fouling & clogging of a flat sheet MBR using bespoke single-channel test cell studied. Industrial & municipal sludge samples characterised by CST, sCOD and rheology. Municipal sludge flux-step fouling trends comparable with published literature trends. Only industrial sludge samples displayed clogging (sludging) propensity. Sludging likely to relate to rheological impacts on air scouring at high SS levels.